Aerobic exercise increases hippocampal volume in older women with probable mild cognitive impairment: a 6-month randomised controlled trial. Issue 4 (7th April 2014) - ten Brinke, Lisanne F; Bolandzadeh, Niousha; Nagamatsu, Lindsay S; Hsu, Chun Liang; Davis, Jennifer C; Miran-Khan, Karim; Liu-Ambrose, Teresa
Abstract : Background: Mild cognitive impairment (MCI) is a well-recognised risk factor for dementia and represents a vital opportunity for intervening. Exercise is a promising strategy for combating cognitive decline by improving brain structure and function. Specifically, aerobic training (AT) improved spatial memory and hippocampal volume in healthy community-dwelling older adults. In older women with probable MCI, we previously demonstrated that resistance training (RT) and AT improved memory. In this secondary analysis, we investigated: (1) the effect of RT and AT on hippocampal volume and (2) the association between change in hippocampal volume and change in memory. Methods: 86 women aged 70–80 years with probable MCI were randomly assigned to a 6-month, twice-weekly programme of: (1) AT, (2) RT or (3) balance and tone training (BAT; ie, control). At baseline and trial completion, participants performed a 3T MRI scan to determine hippocampal volume. Verbal memory and learning were assessed by Rey's Auditory Verbal Learning Test. Results: Compared with the BAT group, AT significantly improved left, right and total hippocampal volumes (p≤0.03). After accounting for baseline cognitive function and experimental group, increased left hippocampal volume was independently associated with reduced verbal memory and learning performance as indexed by loss after interference (r=0.42, p=0.03). Conclusions: Aerobic training significantly increased hippocampal volume in older women with probable MCI. More research is needed to ascertain the relevance of exercise-induced changes in hippocampal volume on memory performance in older adults with MCI. Trail registration number: NCT00958867.